2013
DOI: 10.1016/j.nucengdes.2013.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of wetted area fraction in subcooled pool boiling of water using infrared thermography

Abstract: The wetted area fraction in subcooled pool boiling of water at atmospheric pressure is measured using the DEPIcT (DEtection of Phase by Infrared Thermography) technique. DEPIcT exploits the contrast in infrared (IR) light emissions between wet and dry areas on the surface of an IRtransparent heater to visualize the instantaneous distribution of the liquid and gas phases in contact with the heater surface. In this paper time-averaged wetted area fraction data in nucleate boiling are reported as functions of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…It is known that at heat fluxes close to CHF dry spots are continuously forming on the boiling surface and getting rewetted by the surrounding liquid 6 8 25 33 34 35 . As also indicated by our infrared visualization of the boiling substrate, the boiling crisis is characterized by one or more of these localized dry spots spreading irreversibly and enveloping the entire heated surface in a continuous vapour layer.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that at heat fluxes close to CHF dry spots are continuously forming on the boiling surface and getting rewetted by the surrounding liquid 6 8 25 33 34 35 . As also indicated by our infrared visualization of the boiling substrate, the boiling crisis is characterized by one or more of these localized dry spots spreading irreversibly and enveloping the entire heated surface in a continuous vapour layer.…”
Section: Resultsmentioning
confidence: 99%
“…This is somewhat higher than observed in this study (~82%) and may be due to our use of a highly wetting liquid or a more conductive silicon substrate (ksi~ 120W/m-K). Recently, Kim et al [38] measured the wetted fraction using their DEPIcT technique and also observed irreversible dry spots at CHF using water at a variety of subcoolings. The wetted fraction at saturation reached as low as 50% at CHF, which was much lower than the current results.…”
Section: Discussionmentioning
confidence: 99%
“…These include the work by Kim et al . 31 and Jung et al . 32 using IR thermometry to visualize the liquid-solid interface and measure contact line length, density, and speed.…”
Section: Discussionmentioning
confidence: 92%